A healthy income - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
If you are into conquering new markets, having a stand at a local or regional agricultural trade fair is a good way of extolling the virtues of your goods. If your produce is more suited for export, it is better to team up with others or have others...